2020
DOI: 10.1371/journal.pone.0234657
|View full text |Cite
|
Sign up to set email alerts
|

The fertility effects of public pension: Evidence from the new rural pension scheme in China

Abstract: Public pension insurance has become a major form of social protection around the world. However, little is known about the association between public pension expansion and individuals' fertility in developing economies. In this paper, we examine the effects of the New Rural Pension Scheme (NRPS) on the fertility of married women in rural China. Using data from the China Family Panel Studies (CFPS), the difference-indifferences approach is employed to estimate the impact of NRPS expansion on fertility outcomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Previous studies have suggested that a variety of social security programs may alter financial incentives regarding fertility ( 30 , 31 ). We captured this effect with three measures: a maternity insurance dummy (1 if the respondent was covered by maternity insurance), a health insurance dummy (1 if the respondent was covered by any type of social health insurance), and a public pension dummy (1 if the respondent participated in the governmental pension scheme).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have suggested that a variety of social security programs may alter financial incentives regarding fertility ( 30 , 31 ). We captured this effect with three measures: a maternity insurance dummy (1 if the respondent was covered by maternity insurance), a health insurance dummy (1 if the respondent was covered by any type of social health insurance), and a public pension dummy (1 if the respondent participated in the governmental pension scheme).…”
Section: Methodsmentioning
confidence: 99%
“…Scholars have richly explored the causes of low fertility levels in China, offering explanations in terms of modernization and its associates [e.g., economic development ( Wang and Chi, 2017 ; Yu et al, 2021 ), rising female educational ( Zhao, 2019 ; Chen et al, 2022 ), health ( Clark et al, 2020 ; Zhang, 2020 )], fertility policies ( Jia, 2009 ; Zeng and Hesketh, 2016 ; Zhang, 2017 ), and individual factors ( Wei et al, 2018 ; Shen et al, 2020 ; Wang and Qiao, 2020 ; Zhang et al, 2022 ), respectively. Most of these studies have been analyzed in the framework of economic, wherein the decision to have children is examined based on cost–benefit analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The contributions of this paper are threefold: first, this study improved the theoretical framework of fertility decision-making, as social norms are the bridge between micro-and macro-factors that affect fertility intentions. Second, most existing studies have focused on explaining fertility from an economic perspective ( Wei et al, 2018 ; Zhao, 2019 ; Shen et al, 2020 ; Wang and Qiao, 2020 ; Chen et al, 2022 ; Zhang et al, 2022 ), thus failing to acknowledge human beings as social beings. The individual fertility decision is affected by the social norms of the reference group.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the difference-in-difference model is used for the robustness test (Etinzock and Kollamparambil 2019). The difference-in-difference model can effectively solve the problem of endogeneity among variables (Shen et al 2020). The difference-in-difference method is often used in policy evaluation models (Encina 2013).…”
Section: Did Tests For the Relationship Between Occupational Pension ...mentioning
confidence: 99%